Das modificações, os por quês e os significados das ocupações após a cirurgia cardíaca - MAIA, Emily Farias (2023)
Abstract: The occupations are actions carried out during life, which have form, purpose and meaning. Having undergone cardiac surgery, as well as the postoperative process can influence the engagement of these occupations. In order to investigate this issue, the study sought to understand the occupations of people in the postoperative period of cardiac surgery and its repercussions. It is a qualitative research, of descriptive character, anchored in Occupational Science. It was performed in a Unit of Assistance in Physical Therapy and Occupational Therapy in the North Region of Brazil, having as collaborators twenty-five people who were in the postoperative of cardiac surgery. The results revealed changes in the form, purpose and meaning of occupations. They were removed or modified, followed by dissatisfaction with their fulfillment, as well as the need to engage in meaningful occupations. The research contributed to the construction of scientific knowledge about the occupations of people in the cardiac postoperative period, emphasizing that this process is unique and can have different repercussions in the occupations. Thus, emphasis is placed on the importance of Occupational Therapy within this context by enabling an expanded view of these people, in their physical, psychic, social and also occupational aspects.